Genetic studies in cucumber involving Cucumis hardwickii derived lines and gynomonoecious lines - SINGH, A K; PAN, R S; BHAVANA, P (The Indian Journal of Agricultural Sciences, 2019)
The present investigation which aims to improve fruit yield and widen the genetic base in cucumber by use of Cucumis hardwickii derived lines and gynomonoecious lines was conducted at ICAR-RCER Research Centre, Ranchi during 2002–14. For this purpose crossing was initiated using a C. hardwickii line and cultivated cucumber. Simultaneously, gynoecious condition was transferred to the cultivated cucumber through an exotic collection EC- 399587. Five stable lines from each experiment were obtained after continuous selection and selfing was done up to 10 generations. Twenty eight crosses were made using the four gynomonoecious lines, three C. hardwickii derived lines and a collection from North East. Combining ability studies revealed predominance of non additive gene effects for number of fruits per plant, yield per plant, yield, node at which first female flower appears and days to 50% flowering. HACGM-3, HAC-158 and HAC-159 showed significant GCA effects for number of fruits per plant, yield per plant and yield. It indicated that the increase in number of pistillate flowers in gynomonoecious lines and sequential fruiting habit of C. hardwickii had contributed to the increase in yield and yield components. These genotypes are superior and can be used in cucumber improvement program. Based on SCA effects, hybrid vigour vis-a-vis mean performance and consumer preference, the crosses HACGM-3 × HAC-163 and HAC-160 × HAC-163 were found to be superior and can be directly utilized as promising hybrids. Multivariate analysis of the eight parents based on morphological data grouped them into two main clusters.